Vices in autonomous paternalism: The case of advance directives and persons living with dementia - Um, Sungwoo (Bioethics, 2022)
Advance directives are intended to extend patient autonomy by enabling patients to prospectively direct the care of their future incapacitated selves. There has been much discussion about issues such as whether the future incompetent self is identical to the agent who issues the advance directive or whether advance directives can legitimately secure patient autonomy. However, there is another important question to ask: to what extent and in what conditions is it ethically appropriate for one to limit the liberty or agency of one’s future incompetent self by issuing an advance directive? In this paper, I use a virtue-ethical approach to explore this question, focusing on the case of an advance directive for the future self with moderate dementia. First, I examine virtuous attitudes with regard to autonomy and argue that one can manifest vices or ethically undesirable character traits in trying to intervene in the future self’s life. In particular, I argue that this case can manifest vices such as disdainfulness, intellectual arrogance, and self-dictatorship, which is the vice of trying to control one’s life to an excessive degree, and that a self-dictator fails to give due moral consideration to the future self’s liberty or agency. I then introduce the Daoist idea of wu-wei, which recommends embracement of what happens in one’s life, as one of the possible remedies for the overemphasis on the value of autonomy and control.